5s-2t+7s-9t=

Simple and best practice solution for 5s-2t+7s-9t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5s-2t+7s-9t= equation:


Simplifying
5s + -2t + 7s + -9t = 0

Reorder the terms:
5s + 7s + -2t + -9t = 0

Combine like terms: 5s + 7s = 12s
12s + -2t + -9t = 0

Combine like terms: -2t + -9t = -11t
12s + -11t = 0

Solving
12s + -11t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '11t' to each side of the equation.
12s + -11t + 11t = 0 + 11t

Combine like terms: -11t + 11t = 0
12s + 0 = 0 + 11t
12s = 0 + 11t
Remove the zero:
12s = 11t

Divide each side by '12'.
s = 0.9166666667t

Simplifying
s = 0.9166666667t

See similar equations:

| .3+4x=3x+6 | | -19(-4h-7k+5)= | | 6m-4+6m=-16 | | -3/5=y-1/2 | | (-9*6)+-4= | | 2(6x+130)=5x+164 | | 7(m+7)=40-2m | | 9y+9=15 | | X+x1/2x+1/2x=360 | | (6+2a)=1/2(4a-6) | | 4w-3w+2w+8=-16 | | 5x+6(x+10)=170 | | 15=2a-5a | | n/6=n/2-7/3 | | -4p+4=12 | | 21=-x+4x+9 | | (9*6)+-4= | | 6x-5x=4 | | -9(n-12)=3(1+8n)-12n | | x=40/(x+6) | | y=2x^3-3x^2-36x | | (4/a-2)+(5/a+2)=(5/a^2-4) | | b-5/4=b+2/3 | | -13=3-2x-4 | | -8x(.09)x(-.5)= | | -110=-5x | | 6r-7(4r+2)=28-8r | | 10+5x-7=8x+8-3x | | 3x^3y+3x^2-9x^2y=0 | | 4.50+0.05x=0.2x | | 8n+2=-2n-8 | | p-38=47/5(h-7) |

Equations solver categories